Development of H5P-Based Animated Learning Videos to Stimulate Computational Thinking Skills of Junior High School Students - Kaputri, Aysetu Sindana Mahia; Herlina, Kartina; Rinaldi, Daniel (UNDIKMA, 2025)
The 21st century is marked by technological advancements that are transforming education into more flexible and project-based, with computing thought as a key skill. However, many students still have difficulty understanding computational concepts, such as algorithms, due to less attractive teaching methods. Therefore, learning media innovations, such as H5P-based animated learning videos, are urgently needed. This research uses the Research and Development (R&D) method with a pre-experimental one-group pre-test post-test design in two schools, namely State Junior High School 1 Metro and Muhammadiyah Junior High School 1 Metro. The results of the video development showed a media validity score of 3.91 and material 3.88, both in the very valid category. The effectiveness test showed an average N-Gain of 0.62 (62%), which is classified as moderate in improving computational thinking skills. This animated learning video is suitable for use in the learning process.